2018
DOI: 10.1007/s10578-018-0815-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Parent–Child Discrepancies in Reports of Mental Health Disorders in Young Children

Abstract: The study compares parent and child reports of child mental health to determine the relationship between parent-child disagreement and parental psychological and attitudinal factors, and to determine how parent-child disagreement is associated with the use of specialized services. A cross-sectional study was conducted with 1268 children aged 6-11 years using the Dominic Interactive and the Strengths and Difficulties Questionnaire. Psychological distress and negative parental attitudes were associated with grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 52 publications
5
43
0
Order By: Relevance
“…However, such low child–parent agreement has also observed in a previous study (Liu, Wang, Ji, Cui, & Liu, 2018). It has been reported that greater child–parent agreement would be more easily to be found in children with more severe mental health problems because of the presence of significant symptoms (Bajeux et al, 2018). Because the study sample is a nationally representative school-based sample, we might not observe high child–parent agreement on their reports.…”
Section: Discussionmentioning
confidence: 99%
“…However, such low child–parent agreement has also observed in a previous study (Liu, Wang, Ji, Cui, & Liu, 2018). It has been reported that greater child–parent agreement would be more easily to be found in children with more severe mental health problems because of the presence of significant symptoms (Bajeux et al, 2018). Because the study sample is a nationally representative school-based sample, we might not observe high child–parent agreement on their reports.…”
Section: Discussionmentioning
confidence: 99%
“…Increased reporting of EBPs in their children by mothers with depression have been postulated to be due to possible distortion, with depressed mothers over-reporting EBPs, or to reflect accuracy, such that children of depressed mothers have more EBPs and mothers are accurately reporting on those (81). One study found that parental psychological distress was associated with increased parental report of BPs and EPs as well as increased EPs according to parental and child report combined, thus suggesting that parental psychopathology is associated with both increased child EPs and with possible over-reporting of EBPs by parents (82). Regardless of whether discrepancy is due to distortion or an accurate reflection of CA-HIV EBPs, the discrepancy demonstrated still highlights the need for multi-informant reports (41).…”
Section: Discussionmentioning
confidence: 99%
“…and child perceptions of behavior(Bajeux et al, 2018;Van Roy, Groholt, Heyerdahl, & Clench-Aas, 2010). While it was impossible to examine the child's perspective with the NSCH dataset, it would be important for researchers in the future to assess the child's perspective of flourishment and associated factors.…”
mentioning
confidence: 99%